Can't Compute: Moving Towards an Equitable Digital World - Martin-Bariteau, Florian; Dunn, Suzie; Ahmed, Nasma (Université d'Ottawa | University of Ottawa, 2023)
In today’s society, we all live in a digitally immersive world. While technology brings benefits and conveniences to our daily lives, many forms of technology reinforce individual and systemic biases, and injustices. Digital technologies have been shown to both replicate and amplify existing discriminatory social patterns. Algorithms and artificial intelligence have been shown to reinforce racial and gender stereotypes, social media has been used as a platform to promote hateful and violent speech, and privacy invasive tools, such as internet connected cameras, have been used as surveillance devices against populations already over policed and monitored, notably Black, Indigenous, People of Colour, and members of the LGBTQ2S+ community. Despite these problems, technology has also provided unique opportunities for members of equity seeking groups. Smartphones have been used to capture and expose racist police brutality, social media has been used to build solidarity and social movements, and digital tools have been developed that advance the lifestyles of people living with disabilities. As digitalization increases, we can’t compute an equitable digital context without an understanding of those issues. We need those voices in tech, academic and social spaces. While there is an increase of thought leadership on these issues globally, there is a need to engage more fulsomely in a Canadian-specific context, in order to address the unique history of discrimination, equality, and colonialism from Canadian authors. The Can’t Compute collection of essays aims at bridging this gap in Canadian studies to highlight technology issues that are relevant to members of equality-seeking groups, not simply by exploring those issues but by amplifying voices from those groups unrepresented in mainstream conversation about the digital context. The personal narratives, scholarly articles, and fictional stories in Can’t Compute represent the emerging diversity of topics and voices in the sphere of digital technology. Each piece was written during the early years of the COVID-19 pandemic. A time when global inequities were intensified, there was a resurgence of far-right groups, abusive online behaviour was amplified at higher rates, and dependence on technologies was increasing at unprecedented levels. The impetus for bringing this collection together was to highlight the perspectives of people who work and live at the intersections, as there continues to be a significant gap in representation of these voices and issues in literature on technology, even as it becomes increasingly apparent that members of these equity-seeking groups often face a disproportionate brunt of technology's negative effects. This multidisciplinary collection features a variety of writing styles and formats to describe the ways in which technology affects Black, Indigenous, People of Colour, people living with disabilities, women, gender minorities, and members of the LGBTQ2S+ community. These various vantage points provide an opportunity to explore the difficulties equity-seeking communities face when engaging with technology. In the chapters in this collection, the authors discuss how technological tools both connect people by creating spaces for community building, while also isolating people when digital spaces do not represent them, are not accessible to them, or are unsafe due to harassment and discrimination. The authors of this collection often weave in their lived experiences and social locations into their analysis or narrative, adding critical depth to our understanding of these issues. Cindy Ma, Danielle Lussier, Raine Liliefeldt, and Emily Macrae integrate their personal experiences with the benefits and detriments related to technology. Their stories provide the reader with an insider's view of someone impacted by technology, moving away from the abstract and bringing the issue closer to home. Tamsyn Riddle, Stephanie Jonsson, Lucia Flores Echaiz, and Michelle C. Liu, Brittany C. Singh, and Giovanni C. Giuga’s pieces engage with these issues through a more classic academic and/or legal lens to engage in deep analysis, highlighting issues with technology that are important to the equity-seeking groups they discuss. Finally, GL Barrett’s short story builds on the reader's imagination, bringing them into the possibilities of the future of technology. We hope this collection introduces readers to new ideas about technology and reframes old ones, while inspiring advocacy for a more equitable world. When the words, thoughts, and ideas of all people are not included, the system can’t compute. This collection of chapters written by academics, activists, and storytellers describes a multitude of ways that technology is impacting Black, Indigenous, People of Colour, people living with disabilities, women, gender-minorities, and members of the LGBTQ2S+ community. Equity-seeking groups have found new terrain on the Internet, with people gathering for positive, community-building experiences. However, these same technologies have also caused some of the most serious harms and exacerbated existing discrimination. We hope that these chapters will help inform those researching, developing, and living with digital technologies regarding key issues faced by these equity-seeking groups. This collection builds on the foundational work done by previous authors and advocates, and seeks to inspire more writing, learning, and sharing on these issues in the future.
Keywords: Digital policy; Equity; Artificial intelligence